De novo biosynthesis of sexual pheromone in the labial gland of bumblebee males - Žáček, Petr; Prchalová-Horňáková, Darina; Tykva, Richard; Kindl, Jiří; Vogel, Heiko; Svatoš, Aleš; Pichová, Iva; Valterová, Irena (Chembiochem, 2013)
De novo biosynthesis of male sex pheromone from two bumblebee species (Bombus terrestris and Bombus lucorum) was studied by using in vitro incubations of labial glands (LGs) with radioactive [1,2-(14)C]acetate and deuterated [D(3)]acetate. The labeled substrate was incorporated into several types of compounds, such as terpenic alcohols, fatty acids, esters, and hydrocarbons. A similar incubation of [1,2-(14)C]acetate with fat bodies (FB) led to the formation of fatty acids, triacylglycerols (TAG), and hydrocarbons. To support the results from in vitro incubations, PCR analysis of fatty acid synthase (FAS) transcripts in LG and FB was performed. Relative quantification of FAS transcription levels revealed that the abundance of mRNA from the FAS gene is a function of the age of B. terrestris males. A comparison of the relative FAS mRNA gene transcription level in FB and LGs of B. terrestris and B. lucorum males proved that high biosynthetic activity takes place in the LGs of both species. Together, these results indicate that pheromone components are synthesized de novo in the LG.
Keywords: messenger RNA; Fatty Acid Synthases; sexuální lákadla; radioizotopy uhlíku; Salivary Glands, Minor; deuterium; Fatty Acids; mužské pohlaví; Sex Attractants; Mass Spectrometry; Acetic Acid; kyselina octová; malé slinné žlázy; Fat Body; RNA, Messenger; zvířata; Chromatography, Thin Layer; včely; mastné kyseliny; syntázy mastných kyselin; Carbon Radioisotopes; tukové těleso; Bees; chromatografie na tenké vrstvě; Deuterium; hmotnostní spektrometrie; Male; Animals